Authentication schemes for VANETs: a survey. (1st January 2013) - Das, Abhijit; Roychoudhury, Dipanwita; Bhattacharya, Debojyoti; Srinivasan, Rajavelu; Shorey, Rajeev; Thomas, Tony
In this paper, we make a survey of the known schemes for V2V (vehicle to vehicle) and V2I (vehicle to infrastructure) authentication in VANETs (vehicular ad hoc networks). We consider a variety of safety applications in VANETs, identify authentication as one of the security requirements and discuss the security challenges for these applications. Existing authentication schemes based on digital signatures are discussed along with schemes based on hash chains and hash trees. It has also been shown how the level of security of these schemes is increased by the involvement of a trusted Certification Authority. We also focus on issues pertaining to anonymity, unlinkability, traceability and computation and communication overhead. Finally, we summarise the limitations of the existing authentication schemes in real-life applications and conclude that further research is essential in this area.